Utilizing Autologous Multipotent Mesenchymal Stromal Cells and β-Tricalcium Phosphate Scaffold in Human Bone Defects: A Prospective, Controlled Feasibility Trial. (7th April 2016) - Šponer, Pavel; Filip, Stanislav; Kučera, Tomáš; Brtková, Jindra; Urban, Karel; Palička, Vladimír; Kočí, Zuzana; Syka, Michael; Bezrouk, Aleš; Syková, Eva
Abstract : The purpose of this prospective controlled study was to compare healing quality following the implantation of ultraporous β -tricalcium phosphate, containing either expanded autologous mesenchymal stromal cells (trial group, 9 patients) or β -tricalcium phosphate alone (control group, 9 patients), into femoral defects during revision total hip arthroplasty. Both groups were assessed using the Harris Hip Score, radiography, and DEXA scanning at 6 weeks and 3, 6, and 12 months postoperatively. A significant difference in the bone defect healing was observed between both groups of patients (P < 0.05 ). In the trial group, trabecular remodeling was found in all nine patients and in the control group, in 1 patient only. Whereas, over the 12-month follow-up period, no significant difference was observed between both groups of patients in terms of the resorption of β -tricalcium phosphate, the significant differences were documented in the presence of radiolucency and bone trabeculation through the defect (P < 0.05 ). Using autologous mesenchymal stromal cells combined with a β -tricalcium phosphate scaffold is a feasible, safe, and effective approach for management of bone defects with compromised microenvironment. The clinical trial was registered at the EU Clinical Trials Register before patient recruitment has begun (EudraCT number 2012-005599-33 ).